The Influence of Storytelling Marketing and Narrative Transportation on Scarlett Whitening Purchase Decisions: The Mediating Role of Emotional Appeal among Reizuka Ari’s TikTok Viewers - Muhammad Almadini; Amma Fazizah (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
The rapid advancement of digital marketing has transformed brand–consumer communication, particularly on social media platforms such as TikTok, where narrative-based interactions and emotional experiences increasingly shape consumer behavior. However, limited research has examined the emotional mechanisms through which storytelling marketing and narrative transportation influence purchase decisions in TikTok influencer marketing. This study investigates the effects of storytelling marketing and narrative transportation on Scarlett Whitening purchase decisions through the mediating role of emotional appeal among viewers of Reizuka Ari’s TikTok content. A quantitative explanatory design was employed using survey data from 300 respondents selected through purposive sampling. The data were analyzed using partial least squares structural equation modeling (PLS-SEM) with SmartPLS 4.0. The findings demonstrate that storytelling marketing and narrative transportation have significant positive effects on both emotional appeal and purchase decisions. Emotional appeal partially mediates the effects of storytelling marketing and narrative transportation on purchase decisions. The model explains 67.3% of the variance in emotional appeal and 74.8% of the variance in purchase decisions. These findings establish narrative-based communication and emotional engagement as important determinants of consumer decision-making in digital influencer marketing. The study extends Narrative Transportation Theory by demonstrating the role of emotional appeal in short-form video marketing and provides practical guidance for brands and influencers seeking to develop authentic, emotionally engaging, and consumer-centered marketing strategies.